Potential of nanoparticles and nanopolymers in treatment of age-associated diseases. (4th January 2022) - Saadatpour, Fatemeh; Mohammadipanah, Fatemeh; Zohourian, Nazanin; Hodjat, Mahshid
Abstract: Aging is an inevitable process caused by the accumulation of degenerative destructions, which ultimately leads to organism death. As the aging process occurs at the molecular, cellular, and tissue levels, understanding the whole details of age-related disorders is the prerequisite for the development of anti-aging therapy. More than 300 compounds of different sources have been reported with an anti-aging activity that controls age-related diseases through regulating single or multiple signalling pathways. Recent innovations in nanotechniques could lead to the development of nanomaterials having effects on age-associated malfunctions or acting as nanocarrier systems and distributers of anti-aging drugs. In this review, we summarised the molecular mechanisms of longevity and the prospect of developing anti-aging nanomaterials targeting aging pathways.